Sustainability efficiency of Chinese cities involving coal-fired power plants with data envelopment analysis. Issue 5 (3rd September 2017) - Feng, Qiyuan; Qiu, Quanyi; Quan, Yuan; Tang, Lina
ABSTRACT: Coal currently accounts for nearly 70% of the energy consumption in China, and is expected to remain a vital energy source in the near future. Planning and construction of national large-scale coal-fired power plants (CFPPs) is an important aspect of China's 12th coal industry five-year plan and the development strategy for future energy. CFPPs have large electricity generation potential and are important for maintaining energy security and structure. However, the construction and development of CFPPs leads to local ecological and environmental problems. The sustainable development of CFPPs is becoming increasingly important. The assessment of CFPP sustainable development would highlight the main problems in CFPP planning, construction, operation, and management, avoiding the adverse effects on local society, economy, ecosystems, and environment. This study demonstrated a sustainable development assessment framework for CFPPs and their regions, which concerned natural resources and environmental pollutants as the inputs and human well-being as the socio-economic output. Sustainable development would mandate lower inputs and higher well-being outputs. Using data envelopment analysis, the sustainable development efficiency of cities in CFPP regions was assessed. The results showed increases in urban sustainability efficiency for cities involving CFPPs from 1990 to 2010. Heavy water pollution and excess energy consumption were the main problems identified for urban and CFPP sustainable development. The findings of this study can be used as a reference for urban and CFPP sustainable development and provide guidance for future CFPP construction and development.